On the Approximation of Vector Optimization Problems - Norkin, B.V. (Кибернетика и вычислительная техника, 2015)
В работе исследуются условия сходимости приближенного метода решения задач многокритериальной оптимизации, когда целевые функции и допустимое множество заменяются их приближениями. Доказано, что достаточным условием сходимости являются равномерная сходимость приближенных функций к исходной функции и сходимость допустимого множества приближенных задач к допустимому множеству исходной задачи, по крайней мере, в окрестности решения. У роботі досліджено умови збіжності наближеного методу розв'язання задач багатокритеріальної оптимізації у випадку коли цільові функції і допустима область замінюються їх наближеннями. Доведено, що достатньою умовою збіжності є рівномірна збіжність наближених функцій до початкової функції та збіжність допустимої множини наближени We consider an approximation approach to solving vector optimization problems. The standard approach to such problems is to optimize one criterion under constraints on the others or to scalarize the problem, i.e. to combine all criteria into one scalar criterion. This paper describes a completely different approach, where the feasible set is approximated by a discrete grid (deterministic or random) and the vector function is approximately calculated on this grid. The obtained discrete problem is exactly solved by Pareto type optimization. The paper studies conditions for convergence of the approximation method when the objective functions and the feasible set are replaced by their more and more fine approximations.